1986
DOI: 10.1677/joe.0.1090169
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of passive immunization with somatostatin antiserum on adenohypophysial hormone secretions in starved rats

Abstract: The role of somatostatin (SRIF) on adenohypophysial hormone secretion in starved rats was reassessed by passive immunization. Because of the absence of pulsatile GH secretion in starved rats, the effects of the injection of SRIF antiserum on GH levels can be clearly demonstrated. To determine whether starvation modifies the sensitivity of the adenohypophysis to SRIF, we measured 125I-labelled iodo-N-Tyr-SRIF binding. There was no difference in the dissociation constant (Kd) nor in the maximal binding capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 0 publications
4
10
0
Order By: Relevance
“…Williams et al [29] also reported more potent inhibitory effect of SRIH on GH compared to TSH secretion in men. Other supporting evidence has been reported by several investigators, where treatment of animals with SRIF antiserum increases both GH and TSH levels [30][31][32]. However, more marked stimulatory effects of SRIH antiserum on GH compared to TSH levels were observed [31,32].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Williams et al [29] also reported more potent inhibitory effect of SRIH on GH compared to TSH secretion in men. Other supporting evidence has been reported by several investigators, where treatment of animals with SRIF antiserum increases both GH and TSH levels [30][31][32]. However, more marked stimulatory effects of SRIH antiserum on GH compared to TSH levels were observed [31,32].…”
Section: Discussionsupporting
confidence: 68%
“…Other supporting evidence has been reported by several investigators, where treatment of animals with SRIF antiserum increases both GH and TSH levels [30][31][32]. However, more marked stimulatory effects of SRIH antiserum on GH compared to TSH levels were observed [31,32]. Another explanation of the discrepancy between GH and TSH responses is the very weak degree of suppression by isoproterenol on TSH secretion.…”
Section: Discussionsupporting
confidence: 59%
“…In our study TRH-and VIP-induced G H secretion shows a higher sensitivity to the hypothalamic lesion, an effect which parallels the high sensitivity of somatotrophs to SRIF in vivo (22) as well as in vitro (23,24), as compared to that of the other cell types.…”
Section: ~~supporting
confidence: 77%
“…Also consistent with this report, we observed an increase in hypothalamic SS expression in VDD animals. This finding likely reflects the enhanced somatostatinergic tone underlying the decrease in growth hormone in starved animals (22). Cumulatively, these data show that IAADA does not result from a disordered response to negative energy balance but rather to increased activity of inhibitory networks functionally similar to those found in dehydration-induced anorexia (42).…”
Section: Discussionmentioning
confidence: 60%